2005
DOI: 10.1002/ajmg.1320370720
|View full text |Cite
|
Sign up to set email alerts
|

Down syndrome critical region around D21S55 on proximal 21q22.3

Abstract: We have analysed the DNA of 2 patients with many manifestations of Down syndrome and partial duplication of distinct regions of chromosome 21, respectively, q11.205→q22.300 and q22.300→qter (Rahmani et al.: Proceedings of the National Academy of Sciences of the United States of America 86:5958–5962, 1989). Assessment of the copy number of five chromosome 21 sequences (SODI, D21S17, D21S55, ETS2, and D21S15) has shown that D21S55 was duplicated in both cases. The size of the common duplicated region can be esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 26 publications
0
18
0
1
Order By: Relevance
“…In situ hybridization studies show that DYRK1A is highly expressed in brain gray matter, spinal cord, and retina in developing murine embryos (Song et al, 1996;Rahmani et al, 1998;Hämmerle et al, 2003a;Mao et al, 2003;Marti et al, 2003) and in the cerebral cortex, cerebellum, and pyramidal cell layer in the hippocampus in adult mice (Guimera et al, 1996). DYRK1A has been considered a good candidate gene for the Down syndrome phenotypic abnormalities (reviewed in Epstein, 2000;Vicari et al, 2000;Nadel, 2003) due to its localization in the Down syndrome critical region of chromosome 21 (Rahmani et al, 1989(Rahmani et al, , 1990Delabar et al, 1993;Shindoh et al, 1996;Song et al, 1996), its overexpression in the brain of Down syndrome patients (Guimera et al, 1999), and the neurobehavioral alterations shown by transgenic mice overexpressing the gene (Smith and Rubin, 1997;Altafaj et al, 2001). The recent observation that the size of dendrites in some brain areas is reduced in DYRK1A haploinsufficient mice indicates that DYRK1A dose reduction could affect the length and the complexity of the dendrites (Fotaki et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In situ hybridization studies show that DYRK1A is highly expressed in brain gray matter, spinal cord, and retina in developing murine embryos (Song et al, 1996;Rahmani et al, 1998;Hämmerle et al, 2003a;Mao et al, 2003;Marti et al, 2003) and in the cerebral cortex, cerebellum, and pyramidal cell layer in the hippocampus in adult mice (Guimera et al, 1996). DYRK1A has been considered a good candidate gene for the Down syndrome phenotypic abnormalities (reviewed in Epstein, 2000;Vicari et al, 2000;Nadel, 2003) due to its localization in the Down syndrome critical region of chromosome 21 (Rahmani et al, 1989(Rahmani et al, , 1990Delabar et al, 1993;Shindoh et al, 1996;Song et al, 1996), its overexpression in the brain of Down syndrome patients (Guimera et al, 1999), and the neurobehavioral alterations shown by transgenic mice overexpressing the gene (Smith and Rubin, 1997;Altafaj et al, 2001). The recent observation that the size of dendrites in some brain areas is reduced in DYRK1A haploinsufficient mice indicates that DYRK1A dose reduction could affect the length and the complexity of the dendrites (Fotaki et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The human Dyrk1A gene maps to the 21q22.2 region of chromosome 21, in the Down syndrome critical region (Rahmani et al, 1989(Rahmani et al, , 1990Delabar et al, 1993;Shindoh et al, 1996;Song et al, 1996), and transgenic mice harboring an extra copy of this gene exhibit cognitive deficits and motor abnormalities characteristic of Down syndrome (Smith and Rubin, 1997;Altafaj et al, 2001). The human and rodent Dyrk1A gene are ubiquitously expressed in adult and fetal tissues with high expression in the brain and the heart during development (Guimera et al, 1996(Guimera et al, , 1999Song et al, 1996;Rahmani et al, 1998;Hämmerle et al, 2003a;Mao et al, 2003;Marti et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The "few critical genes" hypothesis predicts that a small number of triplicated genes causes the growth, developmental, and cognitive abnormalities characteristic of the condition. Indeed, previous studies mapped DS phenotypes to a genomic region known as the DS critical region (DSCR) (Rahmani et al 1990; for review, see Rachidi and Lopes 2007). DSCR1, located in this region, was shown to protect individuals with DS from developing solid tumors (Baek et al 2009).…”
mentioning
confidence: 99%
“…Dans une première étape, pour faciliter l'étude de la pathogenèse du syndrome, les chercheurs ont tenté de cibler les gènes à étudier en priorité. L'étude des corrélations génotype-phénotype des rares cas de trisomie 21 partielles dues à la mauvaise ségrégation de translocations parentales ou d'inversions (environ 1 % des cas de trisomie 21) a rapidement conduit à l'identification d'une région sur le bras long du chr 21, comprenant la bande q22, supposée être suffisante pour entraîner la majorité des signes cliniques du syndrome de Down [31][32][33][34]. Cette région a été appelée DSCR, pour Down syndrome critical region.…”
Section: La Carte Physique Du Chromosome 21unclassified